KONSTRUKSI KALIMAT KESANTUNAN BERBAHASA - Iswara, Agus Ari; J. Sastaparamitha, Ni Nyoman (Sphota : Jurnal Linguistik dan Sastra, 2019)
This research aims in analyzing about politeness of STMIK STIKOM Indonesia?s students and lecturers based on their sentence construction in communicating on social media. The data was collected from documentation of their conversation on social media in two semesters of 2017 until 2018. Theory of Pragmatic from Wijana and theory of Indonesian Languages from Moelyono and Alwi are applied in this research. The research shows some result. Based on constructions of the sentence, the politeness can be divided by three parameters; those are syntactic form of the sentence, completeness of the sentence element, and word sequence pattern.